PELATIHAN PENGENALAN KEWIRAUSAHAAN BAGI USAHA KECIL AYAM JONTOR BANG RUDI KELURAHAN CIKOKO KECAMATAN PANCORAN JAKARTA SELATAN - Syofriza Syofyan; Henny Setyo Lestari; Srie Wijihastuti (Universitas Trisakti, 2022)
The implementation of PKM (Community Service) aims to improve community /SME understanding of entrepreneurship and provide capital assistance for the continuity of small and medium-sized enterprises during the Covid-19 pandemic. This activity is in the form of counseling and training at The Frozen Chicken UKM and Sambal Uda located on Jl Cikoko Barat No. 49, Pancoran district, South Jakarta. The number of participants who participated in training and counseling activities was 10 SME members who pioneered frozen chicken and chili sauce businesses. They will be given additional funds for business capital to buy adequate equipment in order to serve market demand that has begun to expand outside the province and the use of these funds is accompanied by the Chairman of the Partner. Participants will be given material on tips for resilient entrepreneurship, and how to use social media to promote the resulting product. Thus, it is hoped that this PKM activity can improve participants' understanding and expertise about entrepreneurship.